Utilization of Human papillomavirus (HPV) DNA detection for cervical cancer screening in developing countries: A myth or reality (2013)
Persistent infection by human papillomavirus (HPV) is considered to be the main causative agent of cervical cancer and other anogenital cancers. Of the more than 30 genotypes capable of infecting the anogenital tract, it is estimated that, worldwide, HPV 16 and 18 cause 70% of the cervical cancers. Control through primary prevention has become a distinct reality through a prophylactic vaccine, which may take quite some time for its widespread use. Thus control of cervical cancer through cervical screening strategy is the only viable solution now. Despite the high rates of false negative results associated with cervical cytology, it is still considered as the gold standard for cervical cancer screening in developing countries. The advent of highly sensitive and specific HPV DNA detection techniques has offered a lot of promise for cervical cancer prevention. The severe restriction on the availability of infrastructure, resources and funding in developing countries has made it difficult to adopt HPV DNA detection as a routine cervical cancer prevention strategy. This present discourse is a review of relevant literature using internet search engines such as; PubMed and Google. Due to the limitations of Pap smear, there is need to consider HPV DNA detection as a useful adjunct to Pap smear screening, in order to effectively control cervical cancer in developing countries.